APPLICATION OF POLYESTER-BASED MEMBRANES IN PERIODONTAL REGENERATIVE THERAPY: A SYSTEMATIC REVIEW OF CLINICAL STUDIES - Elitsa Sabeva; Dimitar Dochev (Romanian Journal of Oral Rehabilitation)
Background: To successfully regenerate lost tissues in periodontal therapy, the bone defect must be isolated from the surrounding tissues. For this purpose, various types of barrier membranes have been developed and are being applied. Biodegradable membranes of synthetic origin are of particular interest since their properties can be controlled by modifying their composition and structure. Important representatives of this group are the polyester membranes. Aim of the study: This systematic review aims to investigate the types and effectiveness of polyester membranes used in periodontal regenerative therapy over the last ten years according to the published clinical studies. Materials and methods: The advanced search was conducted on 07 February 2025 using the PubMed, Web of Science, and Scopus databases and adhering to PRISMA guidelines. Results: This study included 256 cases, in 42.8% of which a biodegradable barrier membrane made copolymer of polylactic acid with polyglycolic acid (PLA-PGA) was applied. In over 36% of the cases, a polylactic acid (PLA) was used. In 41.8% of the cases, a polyester membrane was applied without bone graft. Conclusions: Polyester membranes are successfully used in periodontal regenerative therapy. They are characterized by high biocompatibility, good barrier function, controlled biodegradability, and suitable mechanical properties. In the last twenty years, PLA or its copolymers have been commonly used in clinical studies, and this type of biodegradable membrane is usually combined with various bone grafts.